The Effectiveness of Probing-Prompting Learning Model using Google Meet Platform on Student's Mathematical Communication Ability - Siti Aisyah; Dwi Ivayana Sari; Ria Faulina (Urogram Studi Pendidikan Matematika, Universitas IVET, 2022)
The purpose of this study was to determine whether the probing-prompting learning model using the google meet platform was effective in improving students' mathematical communication and to find out whether the mathematical communication of students taught by the probing-prompting learning model is higher than the mathematical communication of students taught by conventional learning. The method used is a quantitative research type of experiment. The population in this study were all seventh grade students of SMP Negeri 1 Socah, while the samples in this study were class VII-A as the experimental class and VII-B as the control class. This research was conducted from April to July 2021. The instrument used is an observation sheet on the teacher's ability to manage learning with a probing-prompting learning model using the google meet platform, observation sheet on students' mathematical communication skills taught using the probing-prompting learning model using the google meet platform, as well as pretest and posttest sheets. The effective aspect is shown by the average observation result of the teacher's ability to manage learning with the probing-prompting learning model using the google meet platform of 3.6 which is in the very good category; the average observation result of students' mathematical communication skills who were taught using the probing-prompting learning model using the google meet platform was 62.47% in the high category; and completeness of student learning by 100%. Based on the results of the independent sample t-test, the mathematical communication of students who were taught using the probing-prompting learning model using the google meet platform was higher than the mathematical communication of students who were taught using conventional learning. Keywords: Probing-Prompting Learning Model, Google Meet, Mathematical Communication.